2009
DOI: 10.1103/physrevb.80.094201
|View full text |Cite
|
Sign up to set email alerts
|

Growing correlations and aging of an elastic line in a random potential

Abstract: We study the thermally assisted relaxation of a directed elastic line in a two dimensional quenched random potential by solving numerically the Edwards-Wilkinson equation and the Monte Carlo dynamics of a solid-on-solid lattice model. We show that the aging dynamics is governed by a growing correlation length displaying two regimes: an initial thermally dominated power-law growth which crosses over, at a static temperature-dependent correlation length $L_T \sim T^3$, to a logarithmic growth consistent with an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 61 publications
4
68
0
Order By: Relevance
“…18 This is expected to be different in disordered systems as here a crossover from a transient, preasymptotic, power-law regime to an asymptotic regime with a slower, logarithmic, growth is predicted to happen. 20 There is mounting evidence, due to recent studies of elastic lines in disordered media, [7][8][9] that this crossover indeed takes place. Obviously, this crossover has to be taken into account in order to elucidate the scaling properties of disordered systems relaxing toward equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 This is expected to be different in disordered systems as here a crossover from a transient, preasymptotic, power-law regime to an asymptotic regime with a slower, logarithmic, growth is predicted to happen. 20 There is mounting evidence, due to recent studies of elastic lines in disordered media, [7][8][9] that this crossover indeed takes place. Obviously, this crossover has to be taken into account in order to elucidate the scaling properties of disordered systems relaxing toward equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…New insights into this matter have come very recently through a series of papers on the dynamics of elastic lines in a random potential. [7][8][9] These papers provide convincing evidence for a dynamic crossover between a transient regime, characterized by a power-law growth with an effective dynamical exponent that depends on the disorder, and the asymptotic regime where the growth is logarithmic in time. This result strongly suggests the possibility that a similar crossover could take place in disordered ferromagnets and that the observed power-law regime with nonuniversal dynamical exponents is not the asymptotic regime.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…An especially interesting realisation of such out-of-equilibrium phenomena is provided by quenches, in which a parameter such as temperature or the appropriate conjugate field is abruptly varied. Numerical studies of interfaces subjected to quenches [163,164,165,166,167] have shown ageing of the interface and a longterm memory of the initial configuration. For ferroelectrics, Likodimos et al [95,103] studied domain evolution in cleaved triglycine sulfate crystals ( Fig.…”
Section: Towards More Complex Physics At Domain Wallsmentioning
confidence: 99%
“…In order to define a response, we appeal to the procedures used in irreversible systems [15,17,18,31] where the external field is related to a local change of rates. In the KK model, we consider a space-dependent deposition rate p i = p 0 + a i ε/2 with a i = ±1 and ε = 0.005 a small parameter.…”
mentioning
confidence: 99%